The Implementation of Differentiated Instruction in Mathematics Learning to Overcome Differences in Students’ Cognitive Styles - Grafika Saraswati; Dian Septi Nur Afifah; Setyo Hartanto (PT. Anagata Sembagi Education, 2024)
Differentiated instruction has emerged as a crucial issue in education to address the varying needs of students in the classroom, specifically in mathematics subjects at the junior high school level. This approach highlights the importance of tailoring learning strategies to meet the distinctive needs of each student, taking into account their cognitive style, interests, and level of learning readiness. This study aimed to describe the implementation of the differentiated instruction model. This study employed a descriptive-qualitative approach, with an observation sheet as an instrument for data collection. Data analysis involved data reduction, data presentation, and drawing conclusions, along with validity testing using triangulation techniques. The results showed that the teacher’s implementation of differentiated instruction increased significantly between the first and second meetings, with the percentage of implementations increasing from 85.71% to 92.86%. Students demonstrated various responses based on their cognitive styles: reflective students showed a high level of organization and self-confidence; impulsive students were prompt in providing answers but less accurate; and slow-inaccurate students required more time to process information and frequently made mistakes. The implementation of the differentiated instruction strategy at State Junior High School (SMPN) 2 Sumbergempol has been proven to improve the quality of mathematics learning. This approach can serve as a valuable model for other schools seeking to improve their teaching methods. It was suggested that further research could be carried out over an extended period with long-term impact evaluations, as well as additional training for teachers to implement differentiated instruction strategies effectively.